2009
DOI: 10.1016/j.brainres.2009.01.048
|View full text |Cite
|
Sign up to set email alerts
|

Categorization of biologically relevant chemical signals in the medial amygdala

Abstract: Many species employ chemical signals to convey messages between members of the same species (conspecific), but chemosignals may also provide information to another species (heterospecific). Here, we found that conspecific chemosignals (male, female mouse urine) increased immediate early gene-protein (IEG) expression in both anterior and posterior medial amygdala of male mice, whereas most heterospecific chemosignals (e.g.: hamster vaginal fluid, steer urine) increased expression only in anterior medial amygdal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
93
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(112 citation statements)
references
References 41 publications
16
93
2
1
Order By: Relevance
“…13,14 Many studies using Fos as a marker of neuronal activity have shown strong activation of the MeAm associated with stressful stimuli. 13,15,16 Moreover, inhibition of the MeAm has demonstrated that it does indeed mediate the cardiovascular response to stress in rats, indicating that Fos activity is not merely a response to the stressor.…”
Section: Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 Many studies using Fos as a marker of neuronal activity have shown strong activation of the MeAm associated with stressful stimuli. 13,15,16 Moreover, inhibition of the MeAm has demonstrated that it does indeed mediate the cardiovascular response to stress in rats, indicating that Fos activity is not merely a response to the stressor.…”
Section: Hypertensionmentioning
confidence: 99%
“…Midfrequency BP power was attenuated in both strains (P lesion <0.05) and the depressor responses to pentolinium after enalaprilat pretreatment was attenuated after lesions in BPH/2J mice (P lesion <0.001; n=3 in the integration of olfactory and chemosensory signaling involved in predator and territorial responses and reproduction. 13,14 Many studies using Fos as a marker of neuronal activity have shown strong activation of the MeAm associated with stressful stimuli. 13,15,16 Moreover, inhibition of the MeAm has demonstrated that it does indeed mediate the cardiovascular response to stress in rats, indicating that Fos activity is not merely a response to the stressor.…”
mentioning
confidence: 99%
“…The posterior MeA (MeAp) is particularly important in conspecific or socially relevant responses (Meredith and Westberry, 2004;Samuelsen and Meredith, 2009b), and was the focus of these studies. The MeAp has two functionally distinct subdivisions, the dorsal (MeApd) and ventral (MeApv) subdivisions.…”
Section: Introductionmentioning
confidence: 99%
“…The medial nucleus of the amygdala (MeA) has been particularly implicated in prosocial maternal and sexual behavior, as well as agonistic aggressive behaviors. In rodent models, the MeA is activated by socially relevant cues, such as maternal interaction, mating, pheromones of opposite-sex conspecifics, and predators (Fleming and Walsh, 1994;Kollack-Walker and Newman, 1997;Meredith and Westberry, 2004;Choi et al, 2005;Samuelsen and Meredith, 2009b;Bergan et al, 2014), ablation of the MeA impairs recognition of opposite-sex odors (Petrulis, 2009;Maras and Petrulis, 2010), and activation of MeA afferents induces a gradient of social behavior from mating behavior to aggression (Hong et al, 2014;Unger et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of the MeA in the regulation of male-type social behaviors has been demonstrated in numerous studies (13)(14)(15)(16)(17)(18). Particularly, the MeA plays a significant role in chemosensory information processing (15,16,33,34) as part of the social behavior network in the CNS (35). It relays socially meaningful signals to activate or inhibit various downstream brain sites, such as the MPOA, anterior hypothalamic area (AHA), and VMN, that are more directly involved in the execution of male sexual and aggressive behaviors (14,(36)(37)(38)(39)(40).…”
Section: Discussionmentioning
confidence: 98%